Temporal trend in the national and sub-national burden of cancers attributable to risk factors in Iran from 1990 to 2021: Findings from the global burden of disease study 2021 - Seyede Maryam Mousavi; Sobhan Younesian; Saba Katebian; Ali Golestani; Shaghayegh Khanmohammadi; Sepehr Khosravi; Yasaman Etemadi; Nazila Rezaei; Sina Azadnajafabad; Bagher Larijani (PLoS ONE, 2025)
Background Cancer is among leading causes of death globally and in Iran. However, studies exploring cancer risk factors trends in Iran are scarce. In this study, we provide estimations of risk-attributable cancer burden at the national and subnational levels in Iran from 1990 to 2021. Methods This study utilized data from the Global Burden of Disease (GBD) 2021 Study to estimate cancer-related years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life years (DALYs), and deaths attributable to behavioral, metabolic, and environmental/occupational risks in Iran nationally and subnationally, from 1990 to 2021. Summary exposure values (SEV) were given to assess the level of exposure. All estimations were reported along with 95% uncertainty intervals (UI). Results In 2021, 29.2% (95% UI: 22.9%–35.7%) of cancer deaths, equaling 16,893 (13,332–20,914) deaths and age-standardized rate of 22.66 (17.90–28.14), were attributable to risk factors in Iran. Since 1990, the number of risk-attributable cancer deaths increased by 192% (146% to 242%). Regarding attributable DALYs and deaths, the key risk factors were tobacco, dietary risks, and high body-mass index (BMI), with high BMI and high fasting plasma glucose increasing by two-fold in DALYs. Tracheal, bronchus, and lung cancer, followed by colorectal cancer and stomach cancer, had the highest risk-attributable number of DALYs and deaths in both sexes. The risk-attributable age-standardized DALY rates for ovarian cancer [207% (87%–382%)], thyroid cancer [198% (74%–294%)], and multiple myeloma [192% (98%–349%)] showed the most significant increases. Conclusions The all-age number of cancer deaths attributable to risk factors have increased in Iran. The age-standardized DALY rates attributable to high BMI and high FPG doubled from 1990 to 2021, indicating the emerging role of metabolic risk factors in cancer burden. These insights will guide effective cancer prevention strategies in Iran.